A review on the potential of citrus waste for D-Limonene, pectin, and bioethanol production. Issue 7 (28th May 2017) - John, Indulekha; Muthukumar, Karuppan; Arunagiri, Appusamy
ABSTRACT: Citrus peel waste is a valuable lignocellulosic feedstock for bioethanol production due to its richness in fermentable sugars and low lignin content. Citrus peel contains two major value-added products:d -limonene and pectin.d -Limonene is widely used in food, cosmetics, and pharmaceutical industries. However, it acts as a microbial growth inhibitor for yeast during the fermentation process and hence it has to be removed prior to fermentation. Pectin is used as thickening agent, gelling agent, and stabilizer in the food industry. Since pectin increases the viscosity of the fermentation medium and makes fermentation troublesome, it has to be either extracted or degraded into galacturonic acid using pectinase enzyme. Thus, the removal and recovery of bothD -limonene and pectin from citrus peel are essential for better fermentation. For bioethanol production, pretreatment plays a crucial role in the utilization of citrus peels since the reduction ofd -limonene concentration to less than 0.05% is necessary. This review solely describes the potential of citrus waste for value added products such asd -limonene and pectin and the production of bioethanol from citrus peel waste is discussed in detail.